STUDENTS’ PERCEPTION ON THE USE OF ENGLISH SONGS FOR VOCABULARY DEVELOPMENT - Virtaza, Widiah Sepni; Daud, Afrianto; Aruan, Rumiri Rotua (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This study aims to find out students’ perception on the use of english songs for vocabulary development. This research used a mixed method design, namely by using questionnaires and interviews. The respondents were second-semester students of the English Education Department University of Riau. The technique used in collecting data was 14 item statement questionnaire for 40 students and 5 question interview for 5 respondents who like listening to English songs. The results of the research show that students really like English songs and have a positive perception of English song lyrics as a learning medium for vocabulary development. One way that can be used in teaching vocabulary in class is by using English songs. Based on the results obtained, English songs are very influential in increasing vocabulary. English songs also make students not bored by listening to songs.Keywords: English Songs, Perception, Vocabulary.